2013
DOI: 10.5430/cns.v1n1p10
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of continuous self-improvement interventions

Abstract: Although health care providers advise healthy and chronically ill adults to adopt positive health behaviors, traditional interventions focused on motivation and intention have been largely ineffective. Researchers have tested the ability of continuous self-improvement (CSI), an innovative personal system-based intervention, to affect health behavior change at the individual level. This paper systematically reviews CSI interventions focused on improving health behaviors. A search of multiple databases was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…According to Downs and Black, this tool demonstrated a high internal consistency (Kuder-Richardson test =0.89), good test-retest reliability (0.88), good criterion validity (0.89), and inter-rater reliability (0.75). Additionally, STROBE guidelines were designed as criteria for reporting the observational studies; however, these guidelines were used to assess the methodological rigor of published studies (38). Quality reporting of the individual studies included in this review is provided in online Table S2 (Supplementary file 1) and Table 1.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…According to Downs and Black, this tool demonstrated a high internal consistency (Kuder-Richardson test =0.89), good test-retest reliability (0.88), good criterion validity (0.89), and inter-rater reliability (0.75). Additionally, STROBE guidelines were designed as criteria for reporting the observational studies; however, these guidelines were used to assess the methodological rigor of published studies (38). Quality reporting of the individual studies included in this review is provided in online Table S2 (Supplementary file 1) and Table 1.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…28 The unique feature of individualized weight loss programs facilitated by a wellness coach is delivery of continuous and data-driven feedback to foster behavior change. 29 While intensive programs employing frequent in-person contact are most efficacious, they are unable to reach the estimated 200 million U.S. adults who are overweight or obese as they are expensive and inefficient for widespread scalability. A review of diabetes prevention lifestyle interventions, though they are likely cost-effective, estimates average costs to be approximately $27 000 per quality-adjusted life-year.…”
Section: Cardinal Features Of Successful Weight Management Programs Amentioning
confidence: 99%
“…Our findings are also consistent with a recent systematic review of CSI intervention literature showing improvement in lifestyle and chronic diseases. 11 A similar study in kidney transplant patients found an equally strong effect size (ES=1.4). 12 However, our effect size was calculated to estimate sample size for future study and should be considered a crude estimate based on our small sample size.…”
Section: Discussionmentioning
confidence: 86%
“…A recent systematic review of CSI intervention literature found that it helped change health behaviors, specifically life-style management (exercise and weight loss) and chronic diseases (asthma and kidney transplantation). 11 . CSI is a unique, systems-focused intervention that seeks to change behavior that focuses on patients’ personal systems rather than on their motivation or intention.…”
Section: Introductionmentioning
confidence: 99%